Niemann-pick C1-like 1 (NPC1L1) inhibition and cardiovascular diseases - Pirillo, A.; Catapano, A.; Norata, Giuseppe (Bentham Science Publishers, 2016)
© 2016 Bentham Science Publishers. Circulating levels of cholesterol are derived from either endogenous production or intestinal absorption of dietary and biliary cholesterol. Niemann-Pick C1-Like 1 (NPC1L1) is a transmembrane protein that plays a key role in the intestinal absorption of cholesterol by facilitating its uptake through vesicular endocytosis. NPC1L1 is the molecular target of ezetimibe which binds its extracellular loop and inhibits sterol absorption without affecting the absorption of other molecules. Ezetimibe significantly reduces plasma levels of total and low density lipoprotein cholesterol (LDL-C) as monotherapy or when added to statins, the association with a low dose of statin is of particular interest for patients experiencing statin-related side effects. The recent results of the IMPROVE-IT study, which evaluated the cardiovascular effect of ezetimibe added to simvastatin therapy in subjects who had had an acute coronary syndrome and with LDL-C levels within the recommended range, showed that a further LDL-C lowering reduced the incidence of cardiovascular events. To date, ezetimibe represents the only inhibitor of NPC1L1 available for clinical use, however, novel aminos- lactam ezetimibe derivatives have been synthesized and their efficacy to inhibit NPC1L1 protein and decrease plasma cholesterol levels is under evaluation.